Caribbean Report 22-09-1995 - Crosskill, Hugh (anchor); Beven, Jack (interviewee); Pankow, Robert (correspondent); Coffey, Kendall (interviewee); Cadman, Dan (interviewee); Cuffy, Victor (interviewee); St. Pierre, Allen (interviewee); Richards, Ken (correspondent); Burton, Dan (interviewee); van der Merwe, Casper (interviewee); Springer, Henderson (interviewee) (The British Broadcasting Corporation, 1995)
In this report the Miami Weather Bureau has dismissed fears in the Windward and Leeward Islands that yet another hurricane is on the way. In the US, more than one hundred alleged Jamaican drug traffickers have been arrested following an undercover operation which provided green cards in exchange for cocaine and cash. Kendall Coffey of the US Attorney Office and Dan Cadman, Immigration and Naturalization Services (INS) comment on the operation. In Trinidad, American marines with local police and soldiers carried out a marijuana eradication exercise, codename "Weed-eater". Human rights campaigner Victor Cuffy questions what will be put in place to assist after the US authorities has eradicated all these drugs. However, as the US moves to eradicate marijuana production in the Caribbean, within its own borders it has become its largest cash crop. Allen St. Pierre, Deputy National Director of NORML (National Organization for the Reform of Marijuana Laws) comments on the increase in marijuana production within the US. Republican Congressman Dan Burton is urging US President Bill Clinton to support his anti-Cuba bill following the overwhelming vote in the House of Representatives. In cricket, contrary to press reports, Barbadian cricket Henderson Springer has not been appointed as captain to the South African side, Western Transvaal, for the upcoming season.
1. Headlines with Hugh Crosskill (00:00-00:40)
2. The Miami Hurricane Center discounts fears that another hurricane is on the way (00:41-01:15)
3. Over one hundred alleged Jamaican drug traffickers have been arrested across the US (01:16-03:42)
4. American marines help eradicate Caribbean marijuana production while in the US it is the country's biggest cash crop (03:43-09:15)
Keywords: Hurricanes -- Caribbean Area; Hurricanes -- Forecasting; Drug control -- United States; Drug traffic -- Investigation -- United States; Illegal aliens -- Government policy -- United States; Smugglers -- Jamaica; Drug traffic -- Caribbean Area; Marijuana -- Government policy -- United States; Marijuana -- Social aspects; Economic sanctions, American -- Cuba; United States -- Economic policy -- Political aspects; United States -- Foreign relations -- Cuba; Cuba -- Foreign relations -- United States; Cricket players -- Barbados; Cricket -- South Africa